Kapasitas Hidrolisis Bakteri Pendegradasi Selulosa Dari Ekosistem Mangrove - Ardiansyah Kurniawan; Suci Puspita Sari; Euis Asriani; Andi Kurniawan; Abu Bakar Sambah; Ira Triswiyana; Asep A. Prihanto (Universitas Bangka Belitung, 2019)
Muntok is an area in the west side of Bangka island which has the potential for offshore fishing, mining, and smelting of tin. Tin mining and smelting can affect cellulolytic bacteria as one of the integration in mangroves. Cellulolytic bacteria can increase the availability of degraded carbohydrates for other organisms. Sampling was done from 3 location of mangrove, namely Tembelok Mangrove, Peltim Mangrove, and Sukal Mangrove. Screening and qualitative identification of cellulolytic bacteria is derived from sediment, weathered wood and leaf litter in the Muntok mangrove. 54 bacterial isolates were identified in screening with CMC 1% enriched media. 24 (44.5%) of them had high HC values in the Lugol indicator, and 21 (39%) isolates in the congo-red indicator. Tembelok mangroves had the highest HC values in the sediment samples, while Peltim mangrove on leaf litter and Sukal mangrove on weathered wood. HC values of isolates of cellulolytic bacteria balanced with fungi, which are more popularly utilized for cellulose degradation. Cellulolytic bacteria potential to increase the digestive value of agricultural waste to substitute fish feed ingredients.